Gestión de la cultura organizacional y desempeño docente en la IE N° 5127 Mártir José Olaya. Ventanilla. Lima - Hernández Espinoza , Edelmira (2024)
Today one of the most relevant topics for the achievement of student learning is teaching performance and its relationship with the management of organizational culture. That is the objective of this research to identify the relationship that exists between the management of organizational culture and teaching performance at IE N. 5127 Mártir José Olaya in Ventanilla. For this purpose, the scientific research carried out has a quantitative approach, uses the hypothetical deductive method, ordinal level and is cross-sectional. A descriptive correlational design used a sample of…….teachers allows us, through the application of a technique called the survey and the use of two questionnaires validated by three expert judgments and whose reliability was measured using Cronbach's alpha, to find the results using descriptive statisticians and Spearman's Rho for hypothesis testing, an inferential statistician. After the work, the following results are found r=,516 and p=0.002 less than the decision sigma 0.05, which concludes that there is a moderate significant relationship between the variable: management of organizational culture and teaching performance. With which we say that if there is good management of the organizational culture, teaching performance will be better and learning achievements will be optimal. The dimensions were statistically analyzed: preparation for learning, teaching for learning, participation in school and community management and professionalization and teacher identity.